Human rights are not enough: a critical assessment of challenges of inequality and care for international human rights - Harbour, Sophie (My University, 2019)
This thesis takes human rights and presents two contemporary critiques that find fault in the ability of the concept to adequately address current moral crises and to found a theory of moral reasoning moving forward. What will develop is an argument that human rights are not enough to be the starting point from where we form our ideas of moral theory and political and social policy. They do not provide a framework that recognises the indelibly dependent nature of human existence embodied by the ethics of care and they are ill-equipped to adequately counteract the growing radical inequality which has considerable social, political and moral consequences. Aside from critiquing human rights, an ethics of care also serves as a potential starting point from whence to reassess how we understand political and social realities. It offers insights into how we might approach the question of ‘why inequality matters’ and it is a lens through which I see possibilities of expanding our ideas of motivation, power, vulnerability and language, amongst others
University of Witwatersrand Department of Political Science A thesis submitted for Masters By Research 2019
Keywords: Human rights--South Africa; Civil rights; Apartheid; South Africa--Politics and government